THE INFLUENCE OF WORK DISCIPLINE AND JOB TRAINING ON EMPLOYEE PERFORMANCE AT PT. ISS INDONESIA CENTRAL MANAGEMENT AREA GBK JAKARTA GARDENER SECTION - Afifah, Nur; Tanjung, Asridah Warni; Sunarto, Ading (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This study aims to determine how much influence work discipline and work training have on employee performance at PT. ISS Indonesia GBK Management Center Area Jakarta Gardener Section. The method used in this study is quantitative analysis with a population of employees of PT. ISS Indonesia GBK Management Center Area Jakarta Gardener Section as many as 85 respondents or samples with data collection techniques by distributing questionnaires. The data analysis methods used in this study are (validity test, reliability test and classical assumption test), quantitative descriptive analysis, simple and multiple regression analysis, correlation coefficient analysis, determination coefficient analysis, hypothesis testing (T and F tests). The results of the study of the work discipline variable have a regression coefficient value of 0.696, a t-value of 8.824> t-table 1.988. This means that Ha is accepted and Ho is rejected. The results of the study of the work training variable have a regression coefficient value of 0.650, a t-value of 7.786> t-table 1.988. This means that Ha is accepted and Ho is rejected. So it can be concluded that work discipline and work training have a positive and significant influence on employee performance at PT. ISS Indonesia GBK Jakarta Management Center Area Gardener Section with a calculated F value of 58.562> Ftable 3.11